EFEKTIVITAS PENGGUNAAN SMATRPHONE DALAM MENINGKATKAN MOTIVASI BELAJAR MAHASISWA GEOGRAFI FIS UNP MASA PANDEMI COVID-19 - Dewii, Sisi Supliana; Rahmanelli, Rahmanelli (JURNAL BUANA, 2024)
This study aims to determine the effectiveness of using smartphones in increasing the learning motivation of FIS UNP geography students during the Covid-19 pandemic. This research is classified as a quasy eksperimen research type. The population of all Geography students at Padang State University was 119 students, while the sample used the Probability Sampling technique with the type of random sampling. The data collection technique used a Google Form questionnaire which was distributed online to geography students via the WhatsApp and Gmail applications. The data analysis technique used is descriptive statistics using the N-Gain formula. The results of the data recap were processed using an experimental class system and a control class with pretest and posttest. The results of the study were that geography students' smartphone use to increase learning motivation at FIS UNP in online learning posttest scores in the experimental class had an average of 62.4681 and were in the medium category. Based on hypothesis testing through an independent sample t-test that the effectiveness of smartphone use to increase student learning motivation is 21.7296in the ineffective category.